2005
DOI: 10.1097/01.ede.0000164555.19041.01
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Phthalate Metabolites and Biomarkers of Reproductive Function in Young Men

Abstract: The observed weak associations between 1 phthalate biomarker and impairment of a few aspects of reproductive function biomarkers were not consistent with results from a recent U.S. study. It is not yet possible to conclude whether phthalate exposure may reflect a hazard for human male reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
9
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(146 citation statements)
references
References 20 publications
9
123
9
5
Order By: Relevance
“…This may be related to the much lower production of DEP in Japan (700 tons in 2002 [35]) than in the USA (11,700 tons in 1988 [2]). On the contrary, urinary MnBP concentration was higher in the present study and in European countries [14,36] than in the USA, except for Hoppin et al's [18] study. However, production of DBP was 4,135 tons in Japan [35] and 7,752 tons in USA [3], thus it is unlikely that the difference in MnBP concentration between countries was related to production amount of DBP.…”
Section: Intra-and Interindividual Variations In Urinary Metabolite Ccontrasting
confidence: 87%
“…This may be related to the much lower production of DEP in Japan (700 tons in 2002 [35]) than in the USA (11,700 tons in 1988 [2]). On the contrary, urinary MnBP concentration was higher in the present study and in European countries [14,36] than in the USA, except for Hoppin et al's [18] study. However, production of DBP was 4,135 tons in Japan [35] and 7,752 tons in USA [3], thus it is unlikely that the difference in MnBP concentration between countries was related to production amount of DBP.…”
Section: Intra-and Interindividual Variations In Urinary Metabolite Ccontrasting
confidence: 87%
“…In a recently published study from Sweden, Jonsson et al (2005) recruited 234 young Swedish men at the time of their medical conscript examination. Each man provided a single urine sample used to measure concentrations of MEP, MEHP, MBzP, MBP and phthalic acid.…”
Section: Phthalates (A) Exposurementioning
confidence: 99%
“…(2005) [56] reported that only subjects within the highest quartile for monoethyl phthalate (MEP) had fewer motile sperms, more immotile sperms, and lower luteinizing hormone values, but there was no suggestion of harmful effects for most other endpoints. In the study in China there was no significant difference between phthalate concentrations of semen and sperm density and liveability, while there was a significant positive association between liquefied time of semen and phthalate concentrations of semen [59].…”
Section: R E V I E W P a P E R S Ijomeh 2009;22(4)mentioning
confidence: 99%